Asphalt pavement interlayer systems for structural performance enhancement and fatigue reduction - Karbočius, Martynas; Vaitkus, Audrius (International Conference “Environmental Engineering”, 2023)
One of the possible alternatives to extend the service life of the pavement, reducing the maintenance costs of the pavement and possibly the thickness of the overlay, is the use of grids as a reinforcing interlayer of newly installed asphalt layers. Laboratory studies and the very limited amount of visual observation data from real use cases of grids partially substantiate the effectiveness of this measure in neutralizing the formation of reflecting cracks, but there is a lack of quantitative data on the performance of the renewed pavement structure distressed with fatigue cracking. This article presents the results of periodic structural monitoring of a pavement structure with a stress absorbing membrane interlayer (SAMI) and grid-reinforced overlay. The test section consists of 3 subsections, where SAMI and two different types of grids were installed on the distressed asphalt base layer and overlaid with a conventional asphalt binder course and wearing course. Measurement of the bearing capacity of the pavement structure with a falling weight deflectometer and visual survey of the pavement condition were used to investigate the performance of the renewed pavement structure. The interim results of the 3-year observation show a good structural condition of rehabilitated pavement.
Keywords: falling weight deflectometer; bearing capacity; geogrid; overlay reinforcement; pavement; pavement rehabilitation